Effects of aniline concentrations on the electrical and mechanical properties of polyaniline polyvinyl alcohol blends - Bhadra, J. (2015)
Abstract In this work, we present an exclusive study on the effect of the feeding ratio of the monomer (aniline) on the structural, thermal, mechanical and electrical properties of polyaniline (PANI) polyvinyl alcohol (PVA) blends. The films obtained from the blends are characterised to determine their surface properties and structural morphology (elemental analysis, SEM and FTIR), thermal properties (TGA and DSC) and optical properties (UV–Vis spectroscopy). We study the effects of aniline on the mechanical and electrical properties of the composites by performing tensile, four probe and A.C. conductivity measurements, respectively. The SEM images reveal a heterogeneous distribution of conductive PANI particles in the continuous PVA matrix. During this experiment, the tensile strength of the blend films is maintained with an increase in the amount of aniline (up to 25wt%), and this behaviour is attributed to intermolecular hydrogen bonding between PANI and PVA in the presence of the surfactant DBSA. The potential attraction of the experiment lies in the nature of the conductivity (of the blend films), which is found to increase from 10−8 to 10−3S/cm with a percolation threshold of 0.78wt%.